2008
DOI: 10.1002/adma.200702438
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Bisadducts for Enhanced Open‐Circuit Voltages and Efficiencies in Polymer Solar Cells

Abstract: A fullerene bisadduct can enhance the efficiency of polymer:fullerene bulk heterojunction solar cells. The bisadduct has a LUMO that is 100 meV higher compared to that of [6,6]‐phenyl C61 butyric acid methyl ester (PCBM). This increases the open‐circuit voltage of polymer:fullerene bulk heterojunction solar cells based on poly(3‐hexylthio phene) and bisadduct PCBM to 0.73 V, while maintaining high fill factors and currents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
449
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 583 publications
(477 citation statements)
references
References 23 publications
22
449
2
4
Order By: Relevance
“…Devices made with blends of this fullerene with P3HT show an increase in V oc of 100 meV, with comparable electron mobilities and photocurrent to the P3HT device, despite the fact that bis-PCBM exists as several isomers. 22 Continuing the trend, tris-PCBM adducts have recently been reported as an inseparable multi-isomer blend. As expected the electron affinity is further decreased, and blend devices show an enhancement of photovoltage of 100 meV over the bisadducts.…”
Section: Factors Influencing the Structure And Performance Of Fullerementioning
confidence: 73%
“…Devices made with blends of this fullerene with P3HT show an increase in V oc of 100 meV, with comparable electron mobilities and photocurrent to the P3HT device, despite the fact that bis-PCBM exists as several isomers. 22 Continuing the trend, tris-PCBM adducts have recently been reported as an inseparable multi-isomer blend. As expected the electron affinity is further decreased, and blend devices show an enhancement of photovoltage of 100 meV over the bisadducts.…”
Section: Factors Influencing the Structure And Performance Of Fullerementioning
confidence: 73%
“…80 Of particular note are the ''bisPCBM" acceptors, which demonstrated that the fullerene sphere can actually be improved as an acceptor, due to band modifications, when substituted more than once. 81 Subsequent work on indene-substituted C 60 have proved to be of great interest. 82 To rectify one of the problems with PCBM (namely its tendency to undergo excessive crystallization), research has effectively demonstrated the use of cross-linking groups.…”
Section: Figurementioning
confidence: 99%
“…1(c)). [32][33][34][35] These two materials are therefore useful for extending the range of LUMO levels of fullerenes for the current investigation and may also give insight into degradation mechanisms applicable to BHJ solar cells.…”
Section: Introductionmentioning
confidence: 99%